Policía predictiva en España: aplicación y retos futuros = Predictive policing in Spain : implementation and future challenges - González Álvarez, José Luis (Behavior & Law Journal, 2020)
Public policy decisions must be based on rigorous data analysis carried out through scientific methods and procedures to avoid making decisions based on biased data or erroneous beliefs. The development of algorithms and predictive models applied to crime analysis has allowed the emergence of predictive police, which analyzes a large amount of historical crime data to identify patterns and estimate the probability of future crimes, and to help a clarification of past crimes. Predictive policing has made it possible for the police forces to strengthen the preventive approach over the reactive approach. The current study explains some of the implementations of predictive policing in Spain. The advances in the areas of gender-based violence and homicide will be analyzed in detail. The main objective is to summarize the studies that have been developed in recent years and the limitations and benefits of predictive methodologies.